INTEGRATING HERMENEUTICS IN QUR'ANIC STUDY: A THOUGHT ANALYSIS OF BINTU SHĀṬĪ' - Raihan; Puspita , Intan; Ramadhani, Wali; Alvia Mahira, Putri (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
This article discusses the integration of hermeneutics in Quranic studies. Some Muslim scholars consider hermeneutics to be one of the partners in interpreting the Quran. One of the contemporary Muslim intellectuals who has quite influential hermeneutical ideas is Bintu Syāṭī'. The research in this paper is classified as qualitative literature research with a socio-historical approach and uses Gadamer's theory to analyze the influence of Bintu Syāṭī''s hermeneutical concept. The results of this study conclude two things, namely: first, Bintu Shāṭī''s method of interpretation in her tafsir is influenced by her education and her husband Amīn al-Khūlī so that Bintu Shāṭī''s method in interpreting the Qur'an leans towards literary studies to reveal the bayani of the Qur'an. Second, Bintu Syāṭī' is one of the Muslim hermeneutic figures who adopts the quasi-objective hermeneutic genre.